First impurity powder injection experiments in LHD. (December 2020) - Nespoli, F.; Ashikawa, N.; Gilson, E.P.; Lunsford, R.; Masuzaki, S.; Shoji, M.; Oishi, T.; Suzuki, C.; Nagy, A.; Mollen, A.; Pablant, N.A.; Ida, K.; et al.
Abstract: Injection of impurities in the form of sub-millimeter powder grains is performed for the first time in the Large Helical Device (LHD) plasma, employing the Impurity Powder Dropper (IPD) (Nagy et al., 2018), developed and built by PPPL. Controlled amounts of boron (B) and boron nitride (BN) powder are injected into the helical plasma. Visible camera imaging, UV and charge exchange spectroscopy measurements show that the injected impurities effectively penetrate into the plasma in two different magnetic configurations. The prompt effects of the impurities on the plasma are characterized as the injection rate is scanned. The injected impurities provide a supplemental electron source, causing the plasma density to increase, together with the radiated power. Beneficial effects on the confined plasma temperature are observed at low plasma densities, due to an increased efficiency in NBI power absorption. For n e, a v < 1 0 19 m − 3 the powder grains penetrate deeper into the plasma, as they can be less effectively deflected by the plasma flow in the divertor leg, which they have to cross first as they are injected from the top of the machine. In this case, the created B ions are observed to move outwards from UV spectroscopy and charge exchange measurements, due to the outwards direction of the radial electric field. This makes low density plasmas a better candidate for powder boronization techniques. Highlights: The Impurity Powder Dropper is used for the first time in LHD. Multiple diagnostics confirm the successful injection of B and BN powder in the plasma. The prompt effect of the impurity seeding on the plasma is characterized. SFINCS simulations help the interpretation of B ion transport measurements. Low density plasmas are found to be a better candidate for real-time boronization.